2017
DOI: 10.3847/1538-4357/aa750f
|View full text |Cite
|
Sign up to set email alerts
|

Particle Acceleration in Two Converging Shocks

Abstract: Observations by spacecraft such as ACE, STEREO, and others show that there are proton spectral "breaks" with energy E br at 1-10 MeV in some large CME-driven shocks. Generally, a single shock with the diffusive acceleration mechanism would not predict the "broken" energy spectrum. The present paper focuses on two converging shocks to identify this energy spectral feature. In this case, the converging shocks comprise one forward CME-driven shock on 2006 December 13 and another backward Earth bow shock. We simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
1
15
2
Order By: Relevance
“…The model was then used to make predictions on the gamma-ray and neutrino emission from colliding winds in compact stellar clusters (Bykov et al 2015) and in bow shock wind nebulae (Bykov et al 2019). Wang et al (2017Wang et al ( , 2019 developed a Monte Carlo code to study the acceleration of particles at a pair of colliding shocks. They considered both the case of converging shocks (Wang et al 2017) and that of a faster shock catching up with a slower one (Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was then used to make predictions on the gamma-ray and neutrino emission from colliding winds in compact stellar clusters (Bykov et al 2015) and in bow shock wind nebulae (Bykov et al 2019). Wang et al (2017Wang et al ( , 2019 developed a Monte Carlo code to study the acceleration of particles at a pair of colliding shocks. They considered both the case of converging shocks (Wang et al 2017) and that of a faster shock catching up with a slower one (Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2017Wang et al ( , 2019 developed a Monte Carlo code to study the acceleration of particles at a pair of colliding shocks. They considered both the case of converging shocks (Wang et al 2017) and that of a faster shock catching up with a slower one (Wang et al 2019). In both cases, they concluded that spectral features such as breaks may appear in the spectrum of accelerated particles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy spectral "break" would form at a certain energy point between 1-10MeV. The specific observed parameters and the simulated parameters can be referenced as to the related literatures [12,13,11,14,15]. The thick solid line with a narrow peak at E = 1.43keV represents the initial Maxwellian energy distribution in the upstream region.…”
Section: Pos(icrc2017)102mentioning
confidence: 99%
“…The attainable highest energy particle is depended on the diffusive length of particles scaled by the size of the precursor region [11]. At the converging shocks, the precursor region size will be shorten and fewer and fewer high energy particles gain energies resulting a softer energy at the high energy "tail" [14].…”
Section: Pos(icrc2017)100mentioning
confidence: 99%
“…Ding et al [2] tested the "twin CME" scenario against all large SEP events and western CMEs with speed > 900 kms −1 in solar cycle 23 and found that most of the large SEP events agree with the "twin CME" scenario and many single fast CMEs do not lead to large SEP events. Wang et al [14] investigate the interactions between the CME-driven shock and Earth's bow shock, which can produce the highest attainable proton energy reaching to ∼20MeV, but with a soft energy spectral slope beyond the "break" point at ∼ 5.5MeV. Here, we propose a simulation of the twin-shock interactions for further investigating a high energy "tail" and the energy spectral properties.…”
Section: Introductionmentioning
confidence: 97%